Challenges and strategies for promoting health equity in virtual care: findings and policy directions from a scoping review of reviews. (21st February 2022) - Budhwani, Suman; Fujioka, Jamie; Thomas-Jacques, Tyla; De Vera, Kristina; Challa, Priyanka; De Silva, Ryan; Fuller, Kaitlin; Shahid, Simone; Hogeveen, Sophie; Chandra, Shivani; Bhatia, R Sacha; Seto, Emily; et al.
Abstract: Objective: We sought to understand and synthesize review-level evidence on the challenges associated with accessibility of virtual care among underserved population groups and to identify strategies that can improve access to, uptake of, and engagement with virtual care for these populations. Materials and Methods: A scoping review of reviews was conducted (protocol available at doi: 10.2196/22847). A total of 14 028 records were retrieved from MEDLINE, EMBASE, CINAHL, Scopus, and Epistemonikos databases. Data were abstracted, and challenges and strategies were identified and summarized for each underserved population group and across population groups. Results: A total of 37 reviews were included. Commonly occurring challenges and strategies were grouped into 6 key thematic areas based on similarities across communities: (1) the person's orientation toward health-related needs, (2) the person's orientation toward health-related technology, (3) the person's digital literacy, (4) technology design, (5) health system structure and organization, and (6) social and structural determinants of access to technology-enabled care. We suggest 4 important directions for policy development: (1) investment in digital health literacy education and training, (2) inclusive digital health technology design, (3) incentivizing inclusive digital health care, and (4) investment in affordable and accessible infrastructure. Discussion and Conclusion: Challenges associated with accessibility of virtual care among underserved population groups can occur at the individual, technological, health system, and social/structural determinant levels. Although the policy approaches suggested by our review are likely to be difficult to achieve in a given policy context, they are essential to a more equitable future for virtual care.